(untitled) - 1966-; 1956-; Roberts, Jonathan; 1956-; (Steven Lawrence); Bloom, Steven L.; Johnson, Mark Steven; Keaton, Michael; 1986-; Cross, Joseph; 1964-; Addy, Mark; et al. (Burbank, CA, 1999)
On the verge of making it big, long-struggling musician Jack Frost suddenly realizes hes missing something vital: time with his wife and young son Charlie. But before Jack can make up for lost time, he swerves off an icy mountain road. Then, one cold winters night, Jack magically returns as a walking, talking, ski-slope-shredding snowman. Determined to be the father he always wanted to be, Jack embarks on a quest to show Charlie that when it comes to being totally cool, theres no dad like a snowdad!
Keywords: Drama; Families; Drama; Drama; Fathers; Snowmen; Death; Films for the hearing impaired; DVD-Video discs; Video recordings for the hearing impaired; Feature films